2023
DOI: 10.1186/s12912-022-01158-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigating nurses’ knowledge and attitudes about delirium in older persons: a cross-sectional study

Abstract: Introduction Delirium is the most common emergency for older hospitalized patients that demands urgent treatment, otherwise it can lead to more severe health conditions. Nurses play a crucial part in diagnosing delirium and their competencies facilitate the appropriate treatment and management of the condition. Aim This study aims to enhance the understanding of delirium care by exploring both knowledge and attitudes of nurses toward patients in ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 44 publications
3
12
0
Order By: Relevance
“…Those with a negative or neutral attitude toward delirium were less likely to have good knowledge about delirium than those with a positive attitude. These findings are supported by previous studies ( 29 , 39 ). In line with this study, an earlier study reported that better knowledge was correlated with a positive attitude toward delirium ( 39 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Those with a negative or neutral attitude toward delirium were less likely to have good knowledge about delirium than those with a positive attitude. These findings are supported by previous studies ( 29 , 39 ). In line with this study, an earlier study reported that better knowledge was correlated with a positive attitude toward delirium ( 39 ).…”
Section: Discussionsupporting
confidence: 93%
“…These findings are supported by previous studies ( 29 , 39 ). In line with this study, an earlier study reported that better knowledge was correlated with a positive attitude toward delirium ( 39 ). Health professionals who believed that the delirium screening tool would change delirium care were more likely to have a positive attitude as compared to those who did not, which is consistent with previous studies ( 9 ).…”
Section: Discussionsupporting
confidence: 93%
“…Overall, the knowledge level was found to be inadequately aligned with the increasing clinical impact of delirium on healthcare services [ 5 , 15 ]. Similar levels of poor delirium knowledge have been reported in previous studies in China and the Netherlands [ 14 , 16 ].…”
Section: Discussionsupporting
confidence: 87%
“…For example, a study in the USA revealed low recognition rates for different subtypes of delirium among licensed nurses and nursing assistants [ 26 ]. Similarly, a study by Papaioannou et al found that nurses in departments with a higher incidence of delirium often answered delirium-oriented questions incorrectly [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation